2022
DOI: 10.3390/horticulturae8040311
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost and Its Derivatives against Phytopathogenic Fungi in the Soil: A Review

Abstract: Synthetic chemicals, such as fertilizers and pesticides, are abundantly used in agriculture to enhance soil fertility and prevent the occurrence of diseases, respectively. Many studies have reported a negative influence of these chemicals on the soil environment. Natural sources from earthworms and their products, as a result of vermicomposting, may be considered better alternatives. The aim of this review was to reveal the source of antifungal efficiency of vermicompost and its derivatives, such as vermiwash,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Vermicomposting has emerged as a promising solution due to its ability to recycle organic waste, reduce greenhouse gas emissions, and improve soil health [13,18]. Governments, organizations, and farmers worldwide have increasingly adopted vermicomposting as a viable and eco-friendly method for waste management and agricultural enhancement [19]. Today, vermicomposting continues to be a subject of ongoing research and development.…”
Section: Introductionmentioning
confidence: 99%
“…Vermicomposting has emerged as a promising solution due to its ability to recycle organic waste, reduce greenhouse gas emissions, and improve soil health [13,18]. Governments, organizations, and farmers worldwide have increasingly adopted vermicomposting as a viable and eco-friendly method for waste management and agricultural enhancement [19]. Today, vermicomposting continues to be a subject of ongoing research and development.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in Australia found that plants grown on VCT exhibited growth parameters exceeding those of plants grown on commercial hydroponic solutions, suggesting that VCT is an ecologically friendly alternative to growth substrates in terms of quality (Ansari et al, 2015 ). Equally noteworthy is that the coelomic fluid (CF) of the earthworm Eisenia fetida has been found to contain bioactive compounds with antifungal and insecticidal properties (Gudeta et al, 2022 ), which, inherently, could be an effective factor in resisting pests and suppressing diseases when VCT is used hydroponically. The use of VCT as a pest‐resistant agent in hydroponically grown plants reduces the residue of chemical compost in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Vermicompost is a decomposed organic fertilizer with good physical properties (porosity, water retention, etc.). It is rich in nutrients (nitrogen, phosphorus, potassium, and medium and microelements) and plant growth regulators, such as gibberellins and growth hormones [6,7], and it may be considered as a substrate to replace peat resources. The addition of vermicompost to peat substrate has influenced the biometric parameters of cucumber seedlings, the physiological parameters and the content of minerals in the leaves, and the early and total yield of the plants [8].…”
Section: Introductionmentioning
confidence: 99%